Gambaran pengetahuan dan sikap dokter gigi Terkait diabetes mellitus - Alexandra Vanessa Gunawan; Firstine Kelsi Hartanto (Jurnal Kedokteran Gigi Terpadu, 2022)
Background:Diabetes mellitus (DM) is a chronic metabolic disease that can be life-threatening. The prevalence of DM increases every year along with obesity. There are a lot of oral manifestations of DM so dentists play an important role in the treatment of DM. The most common oral manifestations found in DM patients is periodontal disease which has a two-way relationship with DM. Dentists can also be the first to know the presence of DM in their patients. Therefore, it is important for dentists to have good knowledge and attitudes regarding the oral health of DM patients. Objective:To determine the knowledge profile and attitudes of dentists regarding the oral health of DM patients. Methods:Descriptive observational study using a validated questionnaire consisting of 30 questions about knowledge and 12 statements about the attitude of dentists regarding the oral health of DM patients.. Questionnaires were distributed via google form to dentists who are members of the West Jakarta PDGI. Results:The number of respondents in this study were 62 dentists, members of the West Jakarta PDGI. 100% of respondents agree that DM will affect the wound healing process and cause loose teeth. However, 45.16% of respondents did not agree that periodontal treatment (scaling and root planing) can improve glycemic control in DM patients. Only 46.77% of respondents always do scaling and only 19.35% of respondents do root planing for DM patients. 64.52% of respondents do not always update their knowledge about DM. Conclusion: Most dentists understand the prognosis, complications, and risk factors for DM, but do not really understand that periodontal treatment can help improve glycemic control.